The Emergence of Biosimilars in Indonesia: Guidelines, Challenges and Prospects - Wardiana, Andri; Ningrum, Ratih Asmana (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2016)
According to the Food and Drug Administration (FDA), biosimilar is defined as a product which is highly similar to the reference product without clinically meaningful differences in safety, purity and potency. Indonesia is a developing country which has more than 250 million people. The domestic need of Biosmilar in Indonesia is about 10-20%.Â Even though the need is very high, Indonesia still has not been able to produce Biosimilar independently. To stimulate the domestic production on biosimilar, National Agency for Drug and Food Control (NADFC) Republic of Indonesia has assigned Regulation of Biosimilar as Peraturan Kepala Badan Pengawas Obat Dan Makanan Republik Indonesia Nomor 17 Tahun 2015 Tentang Pedoman Penilaian Produk Biosimilar. The guidance covers the quality requirement and evaluation of Biosimilar products. The Ministry of Health of Indonesia has a strategic plan in biopharmaceutical covering biosimilar which is going to develop in 2015-2025. The strategy is expected to initiate biosimilar production in Indonesia. This review focuses on the guidelines, challenges and prospects biosimilars in Indonesia comparing to other international regulatory bodies.Keywords: Biosimilar, Indonesia, Guidelines, Challenges and Prospects